2020
DOI: 10.1183/23120541.00354-2019
|View full text |Cite
|
Sign up to set email alerts
|

Advanced nursing practice in COPD exacerbations: the solution for a gap in Switzerland?

Abstract: AimThis study aimed to address the need for adaptation of the current model of chronic obstructive pulmonary disease (COPD) care in Switzerland, particularly in regard to acute exacerbations, and how far an integrated approach involving advanced nursing practice can meet those needs.MethodsA state analysis guided by the PEPPA framework was initiated by the Pulmonology Clinic of University Hospital Zürich. Literature describing the current provision of COPD care regarding exacerbations in Switzerland and intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
0
7
0
3
Order By: Relevance
“… 36 , 37 In Switzerland it been suggested that advanced practice nurses may also be able to play a key role within a multi-professional team in future models of care to coordinate patient care across sectors. 38 Increased use of telehealth technologies for pulmonary rehabilitation or remote consultations, likely to have been accelerated by the COVID-19 pandemic, are also providing additional options for care models. 39 , 40 There is a need for a multidisciplinary approach across all stages of the pathway, there is no point in diagnosing patients earlier if they then cannot be appropriately treated or access effective non-pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 In Switzerland it been suggested that advanced practice nurses may also be able to play a key role within a multi-professional team in future models of care to coordinate patient care across sectors. 38 Increased use of telehealth technologies for pulmonary rehabilitation or remote consultations, likely to have been accelerated by the COVID-19 pandemic, are also providing additional options for care models. 39 , 40 There is a need for a multidisciplinary approach across all stages of the pathway, there is no point in diagnosing patients earlier if they then cannot be appropriately treated or access effective non-pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Verschiedene Ansätze versuchen diese Schnittstellenprobleme zu überwinden, etwa Modelle der integrierten Versorgung, in denen Fach-und Hausärzte als Case-Manager fungieren, die eine bedarfsgerechte Versorgung zwischen den Sektoren planen, steuern und überprüfen. Ein weiterer vielversprechender Ansatz scheint der Einsatz von qualifiziertem Pflegepersonal zu sein, das zwischen den Sektoren vermittelt (Advanced Nursing Practice [21]). Der Erfolg solcher Ansätze ist bereits auch in der akutmedizinischen Versorgung belegt [22].…”
Section: Resultsunclassified
“…Die Überführung der körperlichen Aktivität in den Alltag scheint der IG besser zu ge-lingen als der KG. Allerdings erreichen die Patienten nicht die Erfolge von Studienteilnehmern mit anderen Indikationen [21,35].…”
Section: Gruppeunclassified
“…The focus group interview results and our synthesis of the qualitative studies describing the patients' perceptions of exacerbation management are reported elsewhere. 21 Eight qualitative studies describing patient experiences have been identified: five for smoking cessation challenges, [39][40][41][42][43] three for physical activity. [44][45][46] The results of the literature review and the assessment of the health professionals' perspective are described in Supplemental Table 1.…”
Section: Stage 1: Understanding the Behavior In The Contextmentioning
confidence: 99%